ANIMAL STUDIES IN FIELD OF PERIODONTOLOGY: EXPERIMENTAL PERIODONTAL AND PERIIMPLANT DISEASE INDUCTION - Hatice Balcı Yuce (Cumhuriyet University, 2017)
Preclinical studies are crucial in studying the etiology and pathogenesis of human diseases especially diseases with multifactoriel etiology such as diabetes, cardiovascular diseases and periodontitis. Studies in animal models are complementary to in vitro experiments prior to clinical trials. Every model has its own advantage and disadvantage and there is not any model suitable for all kinds of studies. To find the optimal experimental model and animal species is a major issue for researchers. In this mini-review I aimed to review the animal models used in the field of periodontology and a relatively novel field implantology and though very little, to provide guidance for researchers